HEALTH PROBLEMS AND CARE OF ELDERLY WOMEN IN SILIGURI, WEST BENGAL - Roy, Sourajit (ShodhKosh: Journal of Visual and Performing Arts, 2022)
In the line of word wide trend the elderly population in India is also increasing very rapidly. Moreover, unlike the other age group, women population among the older adults supersedes the male population. Majority of these elderly women are widowed, economically dependents on others, suffer from lower social status and less powerful than their male counterpart. In other words, they remain socio-economically in more vulnerable state than elderly male population. In this backdrop, the present proceeds for investigate the health problems, treatment seeking behavior, and the problems involved therein of elderly women. It is found that, majority of the elderly women suffer from multiple health disorders like blood pressure, arthritis, heart diseases, dental problems, etc. Such ailments of the aged women become more severe and recurrent with augmentation of age. Further, the treatment seeking behavior of the elderly women depicts that for major ailments they always prefer allopathic medicine because it is more effective and reliable, though, a substantial section of them also avail homeopathic medicine for minor ailments because it is cheap, has no side effect and effective for some particular diseases. However, majority of the elderly females economically depend on others for treatment as they do not have their own source of income. Such dependency some time leads to negligence of their health by the other family members. Finally, the caring system of the elderly women in present research reveals that though still majority of the respondents get care from traditional care-givers like daughters or daughter-in-laws but a substantial section of them have to depend on husbands or sons for such care.